Analisis Pengaruh Pendidikan Kewirausahaan dan Efikasi Diri Sebagai Motivasi Berwirausaha pada Mahasiswa Pendidikan Ekonomi Universitas Negeri Surabaya - Melliana Putri Rahayu; Riza Yonisa Kurniawan (Jurnal Paedagogy, 2022)
This study aims to analyze the effect of entrepreneurship education and self-efficacy as entrepreneurial motivation for students of Economics education at the State University of Surabaya. The research method was a quantitative causal design. The sample of this research was the students of the Economic Education study program, State University of Surabaya, batch 2020, totaling 66 people who have received the Entrepreneurship Education Course. The research instrument used was a questionnaire. The data analysis technique of this research was multiple regression analysis. The results of this study showed that entrepreneurship education had a positive and significant influence on entrepreneurial motivation. Self-efficacy had a positive and significant impact on entrepreneurial motivation in students, and entrepreneurship education and self-efficacy had a simultaneous effect on the entrepreneurial basis in Economics education students, State University of Surabaya.